Automated CO2 and CH4 monitoring system for continuous estimation of degassing related to hydropower - Deblois, C. P.; Demarty, M.; Bilodeau, F.; Tremblay, A. (Frontiers in Environmental Science, 2023)
Reliable measurement of greenhouse gas emissions from reservoirs is essential for estimating the carbon footprint of the hydropower industry. Among the different emission pathways, degassing downstream of the turbines and spillway is poorly documented mainly because of the safety stakes related to sampling up and downstream the powerplants. The alternative being to sample the water from the turbine inside the station, this study aimed to assemble a custom automated CO2 and CH4 monitoring system (SAGES), especially designed for long-term surveys in hydropower facilities, with a special focus on low maintenance requirements. The SAGES combines infrared and laser technologies with a modular programming approach and run with a specifically designed plexiglass equilibration system (PES) that maintain a permanent headspace and avoid clogging by suspended solids. Although the SAGES is based on commercially available devices, it is the first time they are combined and used with the gas equilibrator. To ensure the reliability of the mounting and to control the quality of the readings, the system was tested in laboratory prior to its installation in generating stations. SAGES and PES performances were compared with those of generic devices available on the market although less adapted to the specific deployments targeted. The SAGES gas partial pressure measurements were accurate and linear in the entire range tested: 0 to 5,000 ppm for pCO2 and 0 to 600 and 10,000 ppm for pCH4. Gas PP measurements were comparable to the reference CO2/CH4 sensor and there was no drift during long term deployment. The SAGES/PES installed in 2021 in cascading generating stations of the Romaine complex collected more than 28,000 datapoints over a 10-month period and required only two maintenances. Results show that the SAGES is a reliable tool that provide long-term CO2 and CH4 dataset in generating stations while requiring minimal energy, care and maintenance. The data collected in turbine water and the recent use of the SAGES in peatland by a collaborative team demonstrate how the SAGES systems can efficiently contribute to the understanding of reservoir carbon cycles.